ESG as a Value‐Creation Tool for Active Investors: A Profile of Inherent Group. Issue 2 (2nd July 2019) - Davis, Tony; Lescott, Beau
Abstract : A growing number of investment managers claim to integrate environmental, social, and governance considerations into their investment strategy and processes, but few have described how they do so in depth. Even fewer reinforce the importance of sustainability within their own firms by becoming a certified 'B Corporation.' This article offers a rare, inside look at how one such value‐oriented manager uses ESG as a tool for differentiated investment sourcing, underwriting, and corporate engagement with the aim of achieving superior risk‐adjusted returns. One of the main arguments of the article—and a key principle of the firm's investment approach—is that ESG, as applied to both corporate strategy and operations, is an important factor in determining a company's cost of capital. The authors present specific examples of their investment process at work, highlighting how active engagement with management on ESG issues can catalyze progress that becomes valued by the capital markets.